Electrocatalytic Hydrogenation Boosted by Surface Hydroxyls‐Modulated Hydrogen Migration over Nonreducible Oxides - Xu, Shi‐Lin; Wang, Wei; Li, Hao‐Tong; Gao, Yu‐Xiang; Min, Yuan; Liu, Peigen; Zheng, Xusheng; Liu, Dong‐Feng; Chen, Jie‐Jie; Yu, Han‐Qing; Zhou, Xiao; Wu, Yuen (Advanced materials (Weinheim), 2025)
The migration of atomic hydrogen species over heterogeneous catalysts is deemed essential for hydrogenation reactions, a process closely related to the catalyst's functionalities. While surface hydroxyls‐assisted hydrogen spillover is well documented on reducible oxide supports, its effect on widely‐used nonreducible supports, especially in electrocatalytic reactions with water as the hydrogen source, remains a subject of debate. Herein, a nonreducible oxide‐anchored copper single‐atom catalyst (Cu1/SiO2) is designed and uncover that the surface hydroxyls on SiO2 can serve as efficient transport channels for hydrogen spillover, thereby enhancing the activated hydrogen coverage on the catalyst and favoring the hydrogenation reaction. Using electrocatalytic dechlorination as a model reaction, the Cu1/SiO2 catalyst delivers hydrodechlorination activity 42 times greater than that of commercial Pd/C. An integrated experimental and theoretical investigation elucidates that surface hydroxyls facilitate the spillover of hydrogen intermediates formed at the Cu sites, boosting the coverage of active hydrogen on the surface of the Cu1/SiO2. This work demonstrates the feasibility of surface hydroxyls acting as transport channels for hydrogen‐species to boost hydrogen spillover on nonreducible oxide supports and paves the way for designing advanced selective hydrogenation electrocatalysts. Hydrogen spillover is considered to play a major role in ubiquitous technologies involving hydrogen. However, its application in Earth‐abundant widely‐used non‐reducible oxides is severely limited by much shorter migration distances of atomic hydrogen compared to those in reducible oxides. This study presents a surface hydroxyl modulation strategy to enhance hydrogen migration over nonreducible oxides, promoting electrocatalytic hydrogenation for water purification.